PREFERENSI PENGGEREK POLONG (Etiella zinckenella Tritschke) PADA BEBERAPA VARIETAS TANAMAN BUNCIS (Phaseolus vulgaris Linnaeus) - Padila, Padila; Yunita, Wilma; Pebrianti, Herni Dwinta (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2025)
ABSTRACT Common bean (Phaseolus vulgaris Linnaeus) is one of the fruit vegetables widely consumed by Indonesian people. The productivity of common beans in Jambi Province is relatively low compared to national productivity. One of the pests that attack common bean plants is the pod borer (Etiella zinckenella Treitschke), which requires control. Farmers typically use synthetic insecticides for control, but this method is less effective due to the larvae's behavior of attacking inside the pods. Furthermore, the use of synthetic insecticides can pollute the environment and be harmful to consumers. Therefore, alternative solutions, such as using resistant varieties, are needed. The use of resistant varieties aims to reduce the pest population during plant growth and to decrease the percentage of pod borer attacks. The purpose of this study was to determine the level of E. zinckenella attack on several upright common bean varieties, namely Balitsa Variety I, Balitsa Variety III, and Gypsy. This research was conducted by comparing three treatments: Balitsa I, Balitsa III, and Gypsy varieties. The observation variables included the percentage of infested pods, larval population, pod skin hardness, and pod skin thickness. The results showed that E. zinckenella attacked more common beans with thin and less hard pod skins because they were more susceptible to pest attacks, resulting in a higher percentage of infested pods and larval population. Pod skin thickness and hardness play an important role in the resistance of common bean varieties to E. zinckenella. Keywords : common bean, E. zinckenella, plant resistance